Analisis Kriteria Calon Kepala Negara Perspektif Imam Al-Mawardi - M. Azmi Khirman Fadhlani; Sudirman Suparmin (UNES Law Review, 2023)
Elections are an arena for political contestation in the country. to determine the direction of policy that will be chosen by the leader resulting from the results of the election itself. So our involvement in elections is very necessary so that citizens have political rights, namely the right to vote. So we should have to vote in determining the future leader, because one vote of our choice means a lot for Indonesia in the next five years. Islam as a religion, has clearly provided guidelines for us in determining potential leaders in accordance with the Shari'a, as a real illustration of this is reflected in the behavior of the Prophet Muhammad Sallallahu 'Alahi Wassalam and his companions which until now has been applied and improvised by the leaders around the world. This research tries to analyze the concept of Imam Al-Mawardi's thinking in viewing and determining choices in the 2024 elections for leaders who are in accordance with Islamic guidance based on the criteria expressed by Imam Al-Mawardi. This research is qualitative research using a normative-empirical approach based on library research data (literature review). Based on existing analysis, it shows that the criteria possessed by candidates for head of state in the 2024 elections are clearly visible and are in accordance with the views expressed by Imam Al-Mawardi.